2015
DOI: 10.1007/s13197-015-1712-8
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial approaches for controlling pericarp browning in Litchi (Litchi chinensis) fruit

Abstract: The availability of fruit like litchi has been limited by variability in yield, alternate bearing, seasonal differences and most commonly post harvest problems. The litchi fruit has a very short shelf-life during which red color turns brown which greatly affects the appeal to consumer although not the unique flavor. This review article focuses on the post harvest problems especially browning of litchi. The pericarp of litchi is also sensitive to desiccation and turns brown and brittle once moisture is reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…These results imply that the increasing MDA and H 2 O 2 content stimulated the browning of bamboo shoots during storage. Similar results were obtained with lychee (Litchi chinensis) during storage, who considered that the pericarp browning of harvested lychee fruit was associated with a rapid increase in the content of H 2 O 2 and hydroxyl radicals (Ruenroengklin et al, 2009;Bhushan et al, 2015;Zhang et al, 2018;Yun et al, 2021). H 2 O 2 dramatically stimulates membrane lipid peroxidation, increases the accumulation of ROS, and accelerates the browning of the pericarp of longan (Dimocarpus longan; Lin et al, 2016Lin et al, , 2017Lin et al, , 2020Wang et al, 2018c).…”
Section: Browning During Storagesupporting
confidence: 74%
“…These results imply that the increasing MDA and H 2 O 2 content stimulated the browning of bamboo shoots during storage. Similar results were obtained with lychee (Litchi chinensis) during storage, who considered that the pericarp browning of harvested lychee fruit was associated with a rapid increase in the content of H 2 O 2 and hydroxyl radicals (Ruenroengklin et al, 2009;Bhushan et al, 2015;Zhang et al, 2018;Yun et al, 2021). H 2 O 2 dramatically stimulates membrane lipid peroxidation, increases the accumulation of ROS, and accelerates the browning of the pericarp of longan (Dimocarpus longan; Lin et al, 2016Lin et al, , 2017Lin et al, , 2020Wang et al, 2018c).…”
Section: Browning During Storagesupporting
confidence: 74%
“…The various cultivars of litchi vary widely not only in texture, size, shape, and color due to cultivar differences, but also in the levels of biochemical composition. [2] The fruit is small, round, oval, and borne in loose clusters.…”
Section: Introductionmentioning
confidence: 99%
“…These intermediates can be further converted into coumarin and chlorogenic acid, and also can form CoA esters. Finally, these are converted to flavonoids, lignin, alkaloids and other secondary metabolites 26 . Tang et al found a difference of enzymatic browning unrelated to in Fuji apples.…”
Section: Discussionmentioning
confidence: 99%